VALUE ALLOCATION, IDENTITY FORMATION AND POLITICAL STABILITY IN NIGERIA’S DEMOCRATIC EXPERIENCE (1999-2017) - NWAGBO, Samuel N; ABANEME, Ambrose O (Social Science Research, 2021)
Value allocation has been the primary factor that determines attitude of the citizenry towards the affairs of the state and how they interact among themselves on any background. State and state actors’ attitude over value allocation in Nigeria have created unnecessary identity consciousness and alignment among Nigerians. Pressure, competition and rivalry associated with this is responsible for political instability in the polity even in the era of democracy. This is contrary to democratic ethos of justice, equity, inclusiveness, unity and development. Therefore, this paper interrogated continuous increasing of identity formations (ethnic and religious) like Avengers, Boko Haram, Odua Peoples’ Congress (OPC), Indigenous People of Biafra (IPOB), Fulani Herdsmen, etc. in Nigeria, why these identity formations always contest and struggle for value allocation within the polity and why Nigerian state actors have not been able to engage state machinery in democratic manner to address this development challenges in this dispensation of democracy. Rather it has turned to be a party to the whole political imbroglio. Group theory served as a theoretical framework to guide this investigation, likewise, secondary source of data was utilized while ex-post facto method of data analysis was used to analyse data collected. It was recommended that government should deemphasize ethnic and religious recognition in her value allocation and activities. Military engagement should be abolished in addressing internal problems, in order to reduce level of militarization that citizens experience every day. Value allocation (appointment, promotion, award of contracts, creation of states and local government, provision of infra-structure) should be based on justice, equity, fairness, merit and etc not on ethnic or religious considerations. These will help state and it agencies to create an enduring environment for national integration devoid of identity struggle for a better and stable political system in Nigerian state.